2022
DOI: 10.1109/access.2022.3212735
|View full text |Cite
|
Sign up to set email alerts
|

Features-Based IoT Security Authentication Framework Using Statistical Aggregation, Entropy, and MOORA Approaches

Abstract: The Internet of Thing (IoT) is one of the most imperative technology for all organizations that's play a vital role in many operations, using communication networks, for exchange of data in order to perform a useful task. However, security of IoT devices and data is a major concern. This research work prioritizes the alternatives of security authentication features from studied articles. The multi-objective optimization method based on the ratio analysis (MOORA) is useful in multi-criteria decision making (MCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…H. U. Khan et al, [8] employed the MOORA method and statistical aggregation (SA) to prioritize security authentication features for IoT devices, highlighting the significance of enhancing IoT security and achieving an accuracy improvement of approximately 70% using the SA method. S. S. Goswami et al, [9] employed the AHP-TOPSIS Hybrid MCDM methodology to select the best renewable energy source for power production, addressing complex decision-making scenarios with varying factors and preferences, with potential applicability beyond India.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…H. U. Khan et al, [8] employed the MOORA method and statistical aggregation (SA) to prioritize security authentication features for IoT devices, highlighting the significance of enhancing IoT security and achieving an accuracy improvement of approximately 70% using the SA method. S. S. Goswami et al, [9] employed the AHP-TOPSIS Hybrid MCDM methodology to select the best renewable energy source for power production, addressing complex decision-making scenarios with varying factors and preferences, with potential applicability beyond India.…”
Section: Literature Surveymentioning
confidence: 99%
“…The process of Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method involves the data taken in the Decision matrix as well as the criteria weights obtained from the AHP method. The final rankings from MOORA method using the process described by H. U. Khan et al, [8] are shown in Table 4.…”
Section: Topsismentioning
confidence: 99%